2017
DOI: 10.3389/fevo.2017.00145
|View full text |Cite
|
Sign up to set email alerts
|

The Large Seed Size of Domesticated Lima Beans Mitigates Intraspecific Competition among Seed Beetle Larvae

Abstract: The domestication of beans has selected for larger seeds in cultivated plants compared to their wild relatives. This has not only resulted in an enhanced resource for humans, but also for the insects that feed on these seeds. Seed beetles that attack wild and cultivated seeds often lay several eggs on a single seed. We hypothesized that the larger seed size of domesticated beans will mitigate the competition among the larvae that hatch from these eggs, with important implications for their growth and survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
1
20
1
Order By: Relevance
“…The reason for this is often related to the amount of resource available in larger seeds and the consequences on adult body size and ultimately their fitness 27 . Seed beetles lay several eggs on the same seed, which means that larval competition can be very intense and, as can be expected, is more significant in small seeds 25,26 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The reason for this is often related to the amount of resource available in larger seeds and the consequences on adult body size and ultimately their fitness 27 . Seed beetles lay several eggs on the same seed, which means that larval competition can be very intense and, as can be expected, is more significant in small seeds 25,26 .…”
Section: Introductionmentioning
confidence: 75%
“…Physical and chemical characteristics of the host seed are known to greatly affect beetle performance and behavior 2124 . For example, numerous studies show that when faced with a choice, seed beetles prefer to oviposit on larger than smaller seeds 25,26 . The reason for this is often related to the amount of resource available in larger seeds and the consequences on adult body size and ultimately their fitness 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant traits can affect seed beetle performance and evolution (Abdala‐Roberts & Mooney, ; Campan & Benrey, ; Cuny, Shlichta, & Benrey, ; Kergoat, Delobel, Fédière, Rü, & Silvain, ; Toju & Sota, ). More recently, studies showed how plant traits altered by interactions with leaf herbivores can subsequently affect the interactions with insects that attack flowers and seeds (Hernández‐Cumplido et al, ; McArt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, smaller seeds should limit larval development, affecting adult body sizes, for example, suggesting that phenotypic changes in buchines may occur due to the variation in seed size. In fact, some studies have shown that seed size is an important source of phenotypic variation in seed beetles (Toquenaga & Fuji, ; Takakura, ; Amarillo‐Suárez & Fox, ; Cuny et al, ). In addition, the evolution of body size in bruchines can be mediated by the type of competition (scramble or contest) that takes place inside the seeds, which is directly related to the size of the seeds of the host plants (Messina & Karren, ).…”
Section: Introductionmentioning
confidence: 99%